Recruitment of older adults into randomized controlled trials: Issues and lessons learned from two community-based exercise interventions in Shanghai - Lingyan Huang; Jiaojiao Lü; Nan Chen; Yu Liu (Elsevier, 2016)
Background: With the increasing need for high-quality exercise interventions in China, relatively little is known about issues and challenges related to recruitment of older Chinese adults into exercise-based disease prevention interventions. This study aims to describe the recruitment process and outcomes of 2 exercise interventions conducted in Shanghai, China. Methods: Recruitment information was ascertained from 2 community-based randomized controlled trials for 2 exercise interventions, the first designed to improve health outcomes for older women with knee osteoarthritis and the second to study changes in cognitive function in adults with mild cognitive impairment. Results were summarized in terms of recruitment sources, number screened, screening-to-enrollment ratios, and costs. Results: Recruitment was primarily achieved through working with local residential divisions (i.e., neighborhood associations and residential committees). Both studies achieved their planned target number of older adults (45 and 46, respectively) within a 1-year time frame, with a screening-to-randomized ratio of 5:1 and demonstrated excellent retention rates (range 87%-93%) at 6 months. The recruitment cost for the 2 studies averaged RMB 189 (about USD 30) per initial recruit and RMB 738 (about USD 119) per participant randomized. Some major issues encountered during the recruitment process included (1) the use of community neighborhoods to support the conduct of the projects, (2) access to participants, and (3) feasibility. Conclusion: Analysis of the 2 randomized controlled trials has provided valuable insights into the recruitment process and identified resources that can help better planning and recruitment for future interventions. Recommendations aimed at increasing the success of future recruitment efforts are provided.